Fecal microbiota transplant in severe and severe-complicated Clostridium difficile: A promising treatment approach. (4th May 2017) - Fischer, Monika; Sipe, Brian; Cheng, Yao-Wen; Phelps, Emmalee; Rogers, Nicholas; Sagi, Sashidhar; Bohm, Matthew; Xu, Huiping; Kassam, Zain
ABSTRACT: Severe and severe-complicated Clostridium difficile infection (CDI) is associated with high morbidity and mortality. Colectomy is standard of care; however, post-surgical mortality rates approach 50%. Case reports suggest fecal microbiota transplant (FMT) is a promising treatment of severe and severe-complicated disease but there is a paucity of data. Here, we present a single center experience with a novel sequential FMT protocol for patients refractory to maximal medical therapy. This approach consists of at least one FMT delivered via colonoscopy with criteria for repeat FMT and continued vancomycin therapy based on clinical response and pseudomembranes. Our cohort included 57 consecutive inpatients diagnosed with severe or severe-complicated CDI and treated with FMT. Overall, 91% (52/57) experienced clinical cure at 1 month with a 100% cure rate among severe CDI (n = 19) patients and an 87% cure rate for severe-complicated CDI (n = 33) patients. For the cohort, the survival rate was 94.7% at 1 month and 78.6% at 3 months. There were no serious adverse events related to FMT including no procedure-related complications or perforation. There was no difference in outcome between fresh or frozen fecal material. Sequential FMT for inpatients with severe or severe-complicated CDI is promising and may be preferred over colectomy in certain patients.